2020 IEEE International Conference on Artificial Intelligence and Virtual Reality (AIVR) 2020
DOI: 10.1109/aivr50618.2020.00046
|View full text |Cite
|
Sign up to set email alerts
|

Avatars rendering and its effect on perceived realism in Virtual Reality

Abstract: Immersive virtual environments have proven to be a plausible platform to be used by multiple disciplines to simulate different types of scenarios and situations at a low cost. When participants are immersed in a virtual environment experience presence, they are more likely to behave as if they were in the real world. Improving the level of realism should provide a more compelling scenario so that users will experience higher levels of presence, and thus be more likely to behave as if they were in the real worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Another very interesting outcome of our study is that if we can only display locomotion animations, then improving the appearance of the avatars will not increase the overall realism of our simulated crowd. This finding is consistent with a previous study that we performed in an immersive VR emergency experiment, where they studied the differences in realism and presence when improving the appearance of the virtual characters [17].…”
Section: Discussionsupporting
confidence: 92%
“…Another very interesting outcome of our study is that if we can only display locomotion animations, then improving the appearance of the avatars will not increase the overall realism of our simulated crowd. This finding is consistent with a previous study that we performed in an immersive VR emergency experiment, where they studied the differences in realism and presence when improving the appearance of the virtual characters [17].…”
Section: Discussionsupporting
confidence: 92%
“…However, there is ongoing debate on the effect of the visual style on VR-based clinical outcomes. While some studies have found that greater realism in VR correlated with greater immersion and a sense of presence [ 31 , 32 ], others have found that clinical populations preferred simpler and more abstract visuals [ 33 , 34 ]. Future studies should evaluate components of photorealism as they apply to VR experiences and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…When individuals immerse themselves in virtual reality scenarios, their perceptions may mimic those in the real world. 17,18 For example, Martin, V. investigated how acoustic cues are interpreted in virtual reality settings to generate auditory distance judgments and enhance the realism of the virtual sound events within the environment. 19 However, the question of whether the design of virtual reality scenarios can ensure that participants genuinely perceive the plausibility of the scene remains unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Today, virtual reality technology has been employed to aid designers in spatial optimization. When individuals immerse themselves in virtual reality scenarios, their perceptions may mimic those in the real world 17,18 . For example, Martin, V. investigated how acoustic cues are interpreted in virtual reality settings to generate auditory distance judgments and enhance the realism of the virtual sound events within the environment 19 .…”
Section: Introductionmentioning
confidence: 99%